Behavioral Evolution of Drosophila: Unraveling the Circuit Basis - Sato, Kosei (Genes (Basel), 2020)
Behavior is a readout of neural function. Therefore, any difference in behavior among different species is, in theory, an outcome of interspecies diversification in the structure and/or function of the nervous system. However, the neural diversity underlying the species-specificity in behavioral traits and its genetic basis have been poorly understood. In this article, we discuss potential neural substrates for species differences in the courtship pulse song frequency and mating partner choice in the Drosophila melanogaster subgroup. We also discuss possible neurogenetic mechanisms whereby a novel behavioral repertoire emerges based on the study of nuptial gift transfer, a trait unique to D. subobscura in the genus Drosophila. We found that the conserved central circuit composed primarily of fruitless-expressing neurons (the fru-circuit) serves for the execution of courtship behavior, whereas the sensory pathways impinging onto the fru-circuit or the motor pathways downstream of the fru-circuit are susceptible to changes associated with behavioral species differences.